Airway diseases and health literacy (HL) measurement tools: A systematic review to inform respiratory research and practice. Issue 4 (April 2018) - Shum, Jessica; Poureslami, Iraj; Wiebe, Darrin; Doyle-Waters, Mary M.; Nimmon, Laura; FitzGerald, J. Mark; ,
Highlights: Only two out of 65 asthma/COPD HL measurement tools assessed all five HL domains. More than half (n = 49) of the identified tools assessed the 'understand' domain. There was paucity of tools found on assessing a person's ability to 'communicate'. Less than half (n = 30) of the tools identified had been validated. Abstract: Objective: To identify and evaluate asthma/COPD measurement tools that assess any of the five health literacy (HL) domains: (1) access, (2) understand, (3) evaluate, (4) communicate, and (5) use, as well as numeracy. Methods: MEDLINE/Embase (via Ovid) databases from 1974 to 2016 were searched and complimented by grey literature. Study selection and data extraction were conducted by two reviewers independently. Results: We identified 65 tools including 40 asthma, 22 COPD, and 3 asthma/COPD focused tools. Thirty tools had been validated and two assessed all five domains. The 'understand' domain was captured in 49 tools, followed by 'access' in 29 tools, 'use' in 24 tools, 'evaluate' in 20 tools, and 'communicate' in 10 tools. Two tools assessed 'numeracy'. Tool content comprised disease physiology, triggers, symptoms, inhaler technique, self-management practices, and rehab programs. Conclusions: This review highlights paucity of HL tools that have been validated and/or assess the 'communicate' domain and makes a valuable contribution to filling an existing research gap in the field of HL by determining the deficiencies of such tools. Practice implications: Our review uncovers which HL domains are under-measured, justifying the need to develop an airways HL measurement tool which applies the 5-domain model for asthma/COPD management.